Having Linguistic Rules and Knowing Linguistic Facts - Peter Ludlow (Baltic International Yearbook of Cognition, Logic and Communication, 2009)
'Knowledge' doesn't correctly describe our relation to linguistic rules. It is too thick a notion (for example, we don't believe linguistic rules). On the other hand, 'cognize', without further elaboration, is too thin a notion, which is to say that it is too thin to play a role in a competence theory. One advantage of the term 'knowledge'-and presumably Chomsky's original motivation for using it-is that knowledge would play the right kind of role in a competence theory: Our competence would consist in a body of knowledge which we have and which we may or may not act upon-our performance need not conform to the linguistic rules that we know. Is there a way out of the dilemma? I'm going to make the case that the best way to talk about grammatical rules is simply to say that we have them. That doesn't sound very deep, I know, but saying that we have individual rules leaves room for individual norm guidance in a way that 'cognize' does not. Saying we have a rule like subjacency is also thicker than merely saying we cognize it. Saying I have such a rule invites the interpretation that it is a rule for me-that I am normatively guided by it. The competence theory thus becomes a theory of the rules that we have. Whether we follow those rules is another matter entirely.